Influence of work discipline and training on the performance of social service employees, women's empowerment and child protection in Probolinggo - Yatiningrum, Agung (Central Research Institute for Agriculture (CeRIA), 2024)
This research was conducted at the Social Service on Jalan Raya Dringu No. 13 Pabean Village, Dringu District, Probolinggo Regency. The purpose of this study was to determine the effect of work discipline (X1) and training (X2) on employee performance (Y). The type of research used is quantitative research, with a population of 57 employees using data analysis methods, including validity testing, reliability testing, classical assumption testing, multiple regression analysis, analysis of determination (R2) and hypothesis testing using the SPSS 22 statistical program . The results showed that all the validity test results of all variables were valid with results greater than the r table 0.261 and the reliability test results of all variables produced reliable results with results greater than the Cronbach Alpha value of 0.60. The results of this test show that the variable the value of tcount ttable (2.026 > 1.673) (sig. 0.048 0.05) which means that the X2 variable affects the Y variable. The independent variable that has the most dominant influence on the dependent variable with the largest tcount value is the work discipline variable (X1) of 7.486 which is greater than the tcount value of the training variable (X2) of 2.026. this means that the work discipline variable (X1) has the most dominant effect on employee performance.